2017
DOI: 10.1021/acs.nanolett.6b04087
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Mapping of Guided Nanowires by Second Harmonic Generation Polarimetry

Abstract: The growth of horizontal nanowires (NWs) guided by epitaxial and graphoepitaxial relations with the substrate is becoming increasingly attractive owing to the possibility of controlling their position, direction, and crystallographic orientation. In guided NWs, as opposed to the extensively characterized vertically grown NWs, there is an increasing need for understanding the relation between structure and properties, specifically the role of the epitaxial relation with the substrate. Furthermore, the uniformit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…Moreover, the efficient generation of SHG signal, from several ZnO nanostructures, has been reported. For instance, Neeman et al reported crystallographic mapping of ZnO nanowires using the SHG method [25]. Han et al also used the SHG microscopy method to detect the lattice distortion in a bent ZnO nanowire [26].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the efficient generation of SHG signal, from several ZnO nanostructures, has been reported. For instance, Neeman et al reported crystallographic mapping of ZnO nanowires using the SHG method [25]. Han et al also used the SHG microscopy method to detect the lattice distortion in a bent ZnO nanowire [26].…”
Section: Introductionmentioning
confidence: 99%
“…Various semiconducting materials such as GaN 13,[19][20][21] , ZnO [22][23][24] , ZnSe [25][26] , ZnTe 27 , CdSe 28 , CdS [29][30] and CsPbBr3 31 were grown into aligned NW arrays, guided by epitaxial and graphoepitaxial relationships with the substrate. The epitaxial growth is usually driven by the minimization of the mismatch between the NW and the substrate, which controls the growth along specific lattice directions and crystallographic orientation ( Figure.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has reported the horizontal and aligned growth of cesium lead bromide (CsPbBr 3 ) nanowires that form arrays with 6-fold and 2fold symmetries, which reflect the symmetry or morphology of their sapphire substrates 8 . As with standard semiconductors, the assembly of nanowires into ordered arrays facilitated their integration into functional devices and, from a fundamental research standpoint, enables the parallel investigation of multiple highly homogenous nanowires [25][26][27][28][29][30][31][32] . Surface-guided horizontal CsPbBr 3 nanowires constitute an advantageous system for research and applications.…”
mentioning
confidence: 99%